Alocação e operação ótimas de dispositivos de armazenamento de energia visando a operação economica em sistemas de energia com fontes intermitentes - Pontes, Luiz Renato Braz (2019)
This paper presents a method of allocation and optimal operation of energy storage devices in electric power distribution systems with the inclusion of renewable sources, also determining the optimal number to be allocated and the battery optimal cycle of loading and unloading. The method observes the constraints of the electrical network, such as the voltage profile within preset limits, as well as the intermittency of renewable sources based on wind and solar energy. The proposed method was applied to a hypothetical 5-bus network and the IEEE 24-bus distribution network. The results show that the proposed method can extend the life of the batteries and reduce the cost of purchasing electric energy, also has the capacity to improve the distribution of storage energy in the system, due to the optimal allocation.